Antibody screening at reduced pH enables preferential selection of potently neutralizing antibodies targeting SARS‐CoV‐2. Issue 12 (4th October 2021) - Madan, Bharat; Reddem, Eswar R.; Wang, Pengfei; Casner, Ryan G.; Nair, Manoj S.; Huang, Yaoxing; Fahad, Ahmed S.; de Souza, Matheus Oliveira; Banach, Bailey B.; López Acevedo, Sheila N.; Pan, Xiaoli; Nimrania, Rajani; et al.
Abstract: Antiviral monoclonal antibody (mAb) discovery enables the development of antibody‐based antiviral therapeutics. Traditional antiviral mAb discovery relies on affinity between antibody and a viral antigen to discover potent neutralizing antibodies, but these approaches are inefficient because many high affinity mAbs have no neutralizing activity. We sought to determine whether screening for anti‐SARS‐CoV‐2 mAbs at reduced pH could provide more efficient neutralizing antibody discovery. We mined the antibody response of a convalescent COVID‐19 patient at both physiological pH (7.4) and reduced pH (4.5), revealing that SARS‐CoV‐2 neutralizing antibodies were preferentially enriched in pH 4.5 yeast display sorts. Structural analysis revealed that a potent new antibody called LP5 targets the SARS‐CoV‐2 N‐terminal domain supersite via a unique binding recognition mode. Our data combine with evidence from prior studies to support antibody screening at pH 4.5 to accelerate antiviral neutralizing antibody discovery.